Christmas with Southern Living, 2023 : inspired ideas for holiday cooking and decorating. - Cobbs, Katherine (Christmas Southern Living, 2023)
A good resource for the Christmas holiday. Ideas for entertaining, holiday decor and gifting. Includes recipes and ideas for table centerpieces.